Systematic Literature Review: Pengembangan E-Modul Berbasis Augmented Reality untuk Meningkatkan Minat dan Hasil Belajar Biologi - Euis Nur Afidah Euis; Viktor Pandra; Leo Charli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to conduct a literature review on the improvement of students’ learning interest and learning outcomes through the development of Augmented Reality–based learning media. The method used is a Systematic Literature Review (SLR), which aims to identify, evaluate, and interpret evidence from previous studies in order to address the research problem. The results show that, based on the analysis of ten relevant journal articles, the development and use of Augmented Reality–based e-modules are able to increase students’ learning interest and have a positive impact on learning outcomes. In conclusion, the development of Augmented Reality–based learning media is an innovative and effective solution for enhancing students’ learning interest and learning outcomes in the learning process. Keywords: Augmented Reality, learning interest, learning outcomes, media development.